Arctic Flora and Fauna: Recommendations for Conservation Draft #2, April 2002 - Conservation of Arctic Flora and Fauna (CAFF) (Conservation of Arctic Flora and Fauna (CAFF), 2002)
Draft number 2 for Arctic Council working group Conservation of Arctic Flora and Fauna (CAFF)'s Recommendations for Conservation. Presented at the Senior Arctic Officials meeting in Oulu, Finland, May 15-16 2002.